APPLYING THE GRAMMAR TRANSLATION METHOD AND COMMUNICATIVE APPROACH IN TEACHING ENGLISH GRAMMAR - Do‘smamatova Lola Sirojiddin qizi (Journal Park Publishing, 2025)
The Grammar Translation Method (GTM) and Communicative Approach have been widely used approaches in grammar teaching for many years. Which approach is better to apply in teaching foreign grammar - Grammar Translation Method or Communicative Approach? Firstly, this paper aims to explore the history of two approaches and describe the meanings of both of them. Secondly, the paper looks briefly to find out which one is more suitable for teaching by analyzing the results of an experiment that was held in a secondary school. For the experiment, two classes were selected and taught “Present Simple and Present Continuous” using the Grammar Translation Method and Communicative Approach, respectively. The grammar proficiency of the two classes was the same according to pre-test results taken before the experiment, and there was ot no difference between them. However, the post-test results showed that the class that applied the Grammar Translation Method made a significant rise in grammatical competence compared to the other group that applied the Communicative Approach. The results evidenced that the Grammar Translation Method is better than the Communicative Approach in grammar teaching.
Keywords: Grammar Translation Method, Communicative Approach, grammar teaching, approach, pre-test, post-test.